Assessment of CD8 + T Cell Differentiation in Trypanosoma cruzi -Infected Children - Albareda, María Cecilia (2010)
We previously reported that the T cell compartment in chronically Trypanosoma cruzi-infected adult subjects display functional and phenotypic signs of immune senescence. This study aimed to investigate the differentiation and the senescent profile of the overall CD8+ T cell compartment in T. cruzi-infected children at the early stage of the disease. We found a lower percentage of naive (CD27+CD28+CD45RA+) and early antigen-experienced (CD45RA-CD27+CD28+), and higher percentages of late differentiated antigen-experienced (CD45RA -CD27-CD28-) CD8+ T cells in T. cruzi-infected children as compared with age-matched uninfected controls. The expression of the interleukin (IL)-7R is also decreased on naive and on antigen-experienced total CD8+ T cells with various degrees of differentiation. Conversely, the expression of HLA-DR, caspase-3, and CD57 did not vary on the total CD8+ T cell compartment. These findings suggest that the duration of the infection is relevant in the process of immune senescent that this parasite can induce. Copyright © 2010 by The American Society of Tropical Medicine and Hygiene.